2022
DOI: 10.3389/fgene.2022.736988
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K1 Variant Causes Hyperactivation of Wnt4/β-Catenin/FOXL2 Signaling Contributing to 46,XY Disorders/Differences of Sex Development

Abstract: Background: 46,XY disorders/differences of sex development (46,XY DSD) are congenital conditions that result from abnormal gonadal development (gonadal dysgenesis) or abnormalities in androgen synthesis or action. During early embryonic development, several genes are involved in regulating the initiation and maintenance of testicular or ovarian-specific pathways. Recent reports have shown that MAP3K1 genes mediate the development of the 46,XY DSD, which present as complete or partial gonadal dysgenesis. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In PubMed/Medline databases of the last 15 years, 30 patients reported as familial cases of Swyer syndrome were found in whom genetic evaluation was performed [6,15,16,[19][20][21][22][23][24][25][26][27] (Table 1) (method of searching shown in Supplementary Material File S1). The majority of them (27 out of 30) had undergone gonadectomy, and gonadal tumors were present in 18 out of 27 patients (66.6% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…In PubMed/Medline databases of the last 15 years, 30 patients reported as familial cases of Swyer syndrome were found in whom genetic evaluation was performed [6,15,16,[19][20][21][22][23][24][25][26][27] (Table 1) (method of searching shown in Supplementary Material File S1). The majority of them (27 out of 30) had undergone gonadectomy, and gonadal tumors were present in 18 out of 27 patients (66.6% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…FOXL2 and DMRT1 are the critical members of the feminization and masculinization pathways, respectively (Li and Gui, 2018). In mammals, deletion of DMRT1 led to male to female sex reversal (Huang et al, 2017), and knockout of FOXL2 induced the transformation of ovarian cells into testis-like cells (Chen et al, 2022). In P. sinensis, Dmrt1 (Sun et al, 2017) and Foxl2 (Jin L. et al, 2022) have been shown to be essential genes for male and female differentiation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…FOXL2 and DMRT1 are the critical members of the feminization and masculinization pathways, respectively ( Li and Gui, 2018 ). In mammals, deletion of DMRT1 led to male to female sex reversal ( Huang et al, 2017 ), and knockout of FOXL2 induced the transformation of ovarian cells into testis-like cells ( Chen et al, 2022 ). In P .…”
Section: Discussionmentioning
confidence: 99%